The Effectiveness of Almond Juice on Breast Milk Volume at Clinic B Bekasi - Vivi Silawati; Risza Choirunissa; Indrayani, Triana (International Journal of Midwifery and Health Sciences, 2023)
Background: Breast milk is the ideal food for newborns because of its unique nutritional properties. Therefore, it is appropriate for every baby to get exclusive breastfeeding until the age of 6 months. To make this happen, the baby's mother must try to increase the volume and quality of her breast milk. These efforts must be supported by providing appropriate nutritional intake for breastfeeding mothers. Purpose: To determine the effectiveness of almond juice on breast milk volume. Methods: Quasi-experiment with pre and post treatment. The sample in this study was 30 people consisting of 15 experimental groups and 15 control groups. The sampling technique used was purposive sampling. The research instrument used direct observation and breast pump. Data were analyzed using descriptive statistics and inferential statistics, namely paired t-tests. Result: The results showed that there was a significant difference in the volume of breast milk before and after the intervention was given. Conclusion: giving almond juice regularly taken 2 times a day for 10 days is effective in increasing the volume of breast milk. Midwives are expected to be even better at providing counseling regarding the fulfillment of balanced nutrition by adding almond juice in increasing the volume of breast milk.